PERAN MASYARAKAT DALAM PEMBANGUNAN TEMBOK LAUT (SEA WALL) (Studi di Desa Maja Kabupaten Lampung Selatan) - Hinfa Mosshananza (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This research was motivated by the role of the people of Maja Village in participating in building the Sea Wall with the local government of South Lampung Regency. This study aims to find out what role the people of Maja Village play in the construction of the Sea Wall in Kalianda District, South Lampung Regency. This research uses a qualitative descriptive approach method based on data sources through interviews with informants, then obeservation in the field, and documentation. Based on the results of the study that the Role of the Community in the Construction of the Sea Wall in Maja Village, South Lampung Regency is First, the role of the Maja village community in building a Sea Wall is carried out in a voluntary way without coercion from other parties. Second, some people in Maja Village whose land is used for the construction of a sea wall (Sea Wall) approximately one meter from the shoreline, residents' houses are used as residences for construction workers, and community residents help remove dust and remove soil from the road so that damage does not occur and pose a threat. The conclusion in this study is that the people of Maja Village, South Lampung Regency, have played an active role in the construction of the Sea Wall and assisted the Regional Government of South Lampung Regency in realizing regional development. Researchers' advice for Maja Village, Kalianda District, South Lampung Regency, it is hoped that the community will continue to be involved in development activities by the Regional Government and help maintain the Sea Wall as much as possible